RENDEMEN DAN PRODUKTIVITAS BARECORE DARI LIMBAH EMPELUR KAYU MERANTI (Shorea sp.) DI PT. SURYA SATRYA TIMUR, KOTA BANJARMASIN, PROVINSI KALIMANTAN SELATAN - Sheila Landus Fitriana Napitupulu; Noor Mirad Sari; Diana Ulfah (Jurnal Sylva Scienteae, 2019)
ABSTRACT. Yield a benchmark of success or failure of a production achievement, while productivity becomes a measure of achievement of production with the desired result. The purpose is to know the yield and productivity of barecore from meranti wood pith waste (Shorea sp.) in PT. Surya Satrya Timur.That method that being used is collection a primary dan secondary data. Primary data were obtained by direct observation and interview. Primary data is conducted on each unit of activity, so it can know the amount of input, output and waste. While the secondary data is the location of research and related institutions to support the research data. The average yield obtained was 32.95% with the highest yield on one repeat to 40.65% and the lowest yield on the fifth repeat of 26.18%. Yield does not have maximum results because the yield is less than 50%. The average productivity gained was 0.95 m3/h with the greatest productivity in the third repeat of 1.66 m3/h and the lowest productivity on the fifth repeat of 0.34 m3/h. Further research is suggested to do further research on the processing of barecore from pith waste of meranti wood (Shorea sp.) in PT. Surya Satrya Timur on the influence of other factors such as machine layout with productivity, the effect of worker's characteristics on productivity and the ratio of yield between meranti sprouts and other wood chips.Keywords: Yield, Productivity, Barecore, Meranti Wood, PithABSTRAK. Rendemen menjadi tolak ukur berhasil atau tidaknya pencapaian suatu produksi, sedangkan produktivitas menjadi pengukur pencapaian produksi dengan hasil yang diinginkan. Tujuan dari penelitian ini untuk mengetahui rendemen dan produktivitas barecore dari limbah empelur kayu meranti (Shorea sp.) di PT. Surya Satrya Timur. Metode penelitian yang digunakan adalah pengumpulan data primer dan data sekunder. Data primer diperoleh dari pengamatan langsung dan wawancara. Data primer dilaksanakan pada masing-masing unit kegiatan, sehingga dapat diketahui besarnya input, output dan limbah. Sedangkan data sekunder merupakan lokasi penelitian dan instansi terkait untuk menunjang data penelitian. Rata-rata rendemen yang diperoleh sebesar 32.95 % dengan rendemen tertinggi pada ulangan ke satu sebesar 40.65 % dan rendemen terendah pada ulangan ke lima sebesar 26.18 %. Rendemen belum memiliki hasil yang maksimal karena rendemen yang dihasilkan kurang dari 50 %. Rata-rata produktivitas yang diperoleh sebesar 0.95 m3/jam dengan produktivitas terbesar pada ulangan ke tiga sebesar 1.66 m3/jam dan produktivitas terendah pada ulangan ke lima sebesar 0.34 m3/jam. Penelitian selanjutnya disarankan melakukan penelitian lanjutan pada pengolahan barecore dari limbah empelur kayu meranti (Shorea sp.) di PT. Surya Satrya Timur mengenai pengaruh faktor-faktor lain seperti tata letak mesin dengan produktivitas, pengaruh karakteristik pekerja terhadap produktivitas dan perbandingan rendemen antara empelur meranti dengan empelur kayu lain.Kata kunci : Rendemen, Produktivitas, Barecore, Kayu Meranti, Empelur